Multi-agent system-based supply chain coordination - Cheong, Lee Fong (2014)
One of the main issues in efficiently integrating a company or industry's supply chain is the difficulty in coordinating all the activities among all the parties involved, mainly because these parties have different and conflicting objectives. It is insufficient to optimize the operations within a single party involved, while the other parties are not operating at optimal conditions, which result in a poor overall system performance. However, establishing the global optimal solution involves tremendous amount of decision making, and in many cases decisions have to be made based on insufficient and constantly changing information. This causes the decision making process to be iterative and thus time consuming. The main aim of the project is to address the coordination and decision-making issues using the Fourth Party Logistics (4PL)1 model and applying the agent technology to automate such tasks, as well as the process flow in the supply chain.